MOTIVASI MAHASISWA UNIVERSITAS RIAU UNTUK BERGABUNG MENJADI PENGURUS ORGANISASI LSMI AL MADANI. ( Studi Kasus Pengurus LSMI Al Madani Periode 2013- 2014) - Sari, Rahmi Purnama; Hidir,, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
LSMI Al Madani is an institution that stood at the Faculty of Social and Political Sciences, University of Riau engaged in the field Islamic spirituality, activities organized by Al Madani LSMI aimed at achieving campus society in accordance with the Civil FISIP the mission they uphold. Al Madani established in 1999. It’s always have a resons for something, including for join to a particular group, each person have their own reason, and that reason is called with motivation, someone would be interested in Al Madani if motivated or be motivated by something or someone. To analyze the data of this study conducted with qualitative methods. This study makes 6 informants to obtain information that necessery during the research, and to see what the motivation of students of the Faculty of Social and Political Sciences to become members of Al Madani. Some of the motivation of the student is, Islamic Adding insight, curiosity, a sense of sympathy with the organization's management. Then there are several driving factors that led students to join in LSMI Al Madani which is, peers, family, and the organization committee of Al Madani itself. It was a motivation for the students of the Faculty of Social and Political Sciences to join in the management of Al Madani.Keywords: Motivation, Institute of Islamic Spirituality, LSMI Al Madani